The Identification for Development Agenda : Its Potential for Empowering Women and Girls - Dahan, Mariana; Hanmer, Lucia (World Bank, Washington, DC, 2015)
Gender inequality and related issues remain a major global challenge, particularly for developing countries. Despite considerable progress on gender equality over recent decades, key gender gaps remain in endowments (health and education), in access to jobs and economic opportunities, and in voice and agency. Lack of data limits ability to assess gender gaps and measure progress toward eliminating them. Successfully addressing the incompleteness of civil registration and vital statistics (CRVS) systems can help fill some of these vital data gaps. In addition, having official personal identification (ID) is an important stepping-stone for women and girls - enabling them to access services, claim their entitlements as citizens, and increase their voice and agency through participation in voting and other politics. Global initiatives such as identification for development (ID4D) promote opportunities to provide women with access to foundational documentation such as birth certificates and expansion of other ways to establish their legal identity. In addition, better data resulting from personal identity registration will advance gender equality policy discussions and planning. This paper examines rates of male and female registration for national identities globally to identify key registration constraints and gaps. The authors find no systematic evidence of gender-based gaps in birth registration; rather, evidence suggests that poverty, social exclusion, and geography may constrain birth registration of both males and females. Drawing on case studies and national-level data, the authors next examine outcomes in specific policy areas: access to financial services, access to social protection schemes, and inclusion in electoral roles and voting. Here, the evidence suggests, adult women face gender-specific barriers in getting ID, sometimes related to inability to obtain foundational documentation such as birth certificates.